Flavonoids from Aurantii Fructus Immaturus and Aurantii Fructus: promising phytomedicines for the treatment of liver diseases - Jianzhi Wu; Guangrui Huang; Yajing Li; Xiaojiaoyang Li (Chinese Medicine, 2020)
Abstract Background Liver diseases and related complications are major sources of morbidity and mortality, which places a huge financial burden on patients and lead to nonnegligible social problems. Therefore, the discovery of novel therapeutic drugs for the treatment of liver diseases is urgently required. Aurantii Fructus Immaturus (AFI) and Aurantii Fructus (AF) are frequently used herbal medicines in traditional Chinese medicine (TCM) formulas for the treatment of diverse ailments. A variety of bioactive ingredients have been isolated and identified from AFI and AF, including alkaloids, flavonoids, coumarins and volatile oils. Main body Emerging evidence suggests that flavonoids, especially hesperidin (HD), naringenin (NIN), nobiletin (NOB), naringin (NRG), tangeretin (TN), hesperetin (HT) and eriodictyol (ED) are major representative bioactive ingredients that alleviate diseases through multi-targeting mechanisms, including anti-oxidative stress, anti-cytotoxicity, anti-inflammation, anti-fibrosis and anti-tumor mechanisms. In the current review, we summarize the recent progress in the research of hepatoprotective effects of HD, NIN, NOB, NRG, TN, HT and ED and highlight the potential underlying molecular mechanisms. We also point out the limitations of the current studies and shed light on further in-depth pharmacological and pharmacokinetic studies of these bioactive flavonoids. Conclusion This review outlines the recent advances in the literature and highlights the potential of these flavonoids isolated from AFI and AF as therapeutic agents for the treatment of liver diseases. Further pharmacological studies will accelerate the development of natural products in AFI and AF and their derivatives as medicines with tantalizing prospects in the clinical application.